Optimizing Coal Reserves at Pit Muara Tiga Besar Utara (MTBU) PT Bukit Asam to Increase Production in 2025 - Faiz, Ahmad Naufal; Darmansyah, Asep (Universitas KH. Abdul Chalim Mojokerto, 2025)
The mining sector plays a vital role in meeting energy needs and contributing to national export revenues. PT Bukit Asam is a key player in the coal supply chain. One of the primary challenges the company faces is the discrepancy between its internal work plan and budget and the government-approved annual work plan and budget for 2025. This research focuses on determining the most effective strategy to boost coal production in one of its major sites, the Muara Tiga Besar Utara (MTBU) pit. The strategic analysis began with the use of PESTEL and VRIO frameworks to evaluate external and internal conditions. Based on this evaluation, two strategic alternatives were developed. A cost-benefit analysis was then used to determine the most suitable option. The results indicate that Alternative 2 optimization of the central pit area is more financially viable, outperforming the other option in key financial indicators such as Net Operating Profit Margin (NOPM), Return on Investment (ROI), and Break-Even Point (BEP). Further evaluation through sensitivity analysis revealed that fluctuations in coal prices and changes in operating costs significantly affect Net Operating Cash Flow (NOCF). The implementation of the chosen strategy is divided into several phases: initial preparation, production optimization, and monitoring and evaluation. Risk mitigation measures include ensuring equipment availability, implementing real-time cost tracking, and managing exposure to price volatility.